2008
DOI: 10.7748/paed.20.10.21.s25
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pain management in children

Abstract: Pain management in children could be improved through increased co-operation between nurses, physicians and parents. Planning time and good routines could facilitate pain management. Education about pain management and children's pain behaviour might also improve nurses' ability to manage pain in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…In a nurse's transition into expert, autonomy is often mentioned as a virtue (Benner, 1984). On the other hand, Gimbler-Berglund, Ljusegren, and Enskär (2008) showed that good cooperation with physicians was a key factor in conducting nursing activities for children in pain. This could be interpreted as a need for the nurse to be secure and confident in his or her knowledge and autonomy to ensure the nursing perspective in the multiprofessional team.…”
Section: Discussionmentioning
confidence: 99%
“…In a nurse's transition into expert, autonomy is often mentioned as a virtue (Benner, 1984). On the other hand, Gimbler-Berglund, Ljusegren, and Enskär (2008) showed that good cooperation with physicians was a key factor in conducting nursing activities for children in pain. This could be interpreted as a need for the nurse to be secure and confident in his or her knowledge and autonomy to ensure the nursing perspective in the multiprofessional team.…”
Section: Discussionmentioning
confidence: 99%
“…Zahlreiche Studien belegen, dass Gesundheits-und Kinderkrankenpfleger/-innen keine (optimale) Schmerzerfassung durchführen [17,29,33]. Grün-de für diese lückenhafte Schmerzerfassung sind fehlendes Wissen, fehlende Erfassungsinstrumente oder die Annahme, dass Schmerzmanagement nicht in den pflegerischen Aufgabenbereich fällt [9,11]. Weiter haben das Alter und die Diagnose des Kindes einen Einfluss auf das Schmerzmanagement der Gesundheitsund Kinderkrankenpfleger/-innen.…”
Section: Originalien Hintergrund Und Fragestellungunclassified
“…According to Gimbler-Berglund et al (2008) the nurse must take the time to establish a relationship and collaborate with the child. This is confirmed by Björk et al (2006); children should be treated empathetically and the caregiver should speak directly to the child.…”
Section: Discussionmentioning
confidence: 99%
“…Pelander et al (2007) and Pelander and Leino-Kilpi (2004) confirmed that the parents' presence contributes to the child's feeling of safety as well as making treatments more easily accepted. Gimbler-Berglund et al (2008) emphasize that it is the parents who have the greatest knowledge about the child. However, the participants in this study considered that this was only possible if the parent was calm as an insecure parent transferred anxiety to the child.…”
Section: Discussionmentioning
confidence: 99%